Artichoke Polyphenols Sensitize Human Breast Cancer Cells to Chemotherapeutic Drugs via a ROS-Mediated Downregulation of Flap Endonuclease 1. (6th January 2020) - Mileo, Anna Maria; Di Venere, Donato; Mardente, Stefania; Miccadei, Stefania
Abstract : Combined treatment of several natural polyphenols and chemotherapeutic agents is more effective comparing to the drug alone in inhibiting cancer cell growth. Polyphenolic artichoke extracts (AEs) have been shown to have anticancer properties by triggering apoptosis or reactive oxygen species- (ROS-) mediated senescence when used at high or low doses, respectively. Our aim was to explore the chemosensitizing potential of AEs in order to enhance the efficacy of conventional chemotherapy in breast cancer cells. We employed breast cancer cell lines to assess the potential synergistic effect of a combined treatment of AEs/paclitaxel (PTX) or AEs/adriamycin (ADR) and to determine the underlying mechanisms correlated to this potential therapeutic approach. Our data shows that AEs/PTX reduced cell proliferation by increasing DNA damage response (DDR) mediated by Flap endonuclease 1 (FEN1) downregulation that results into enhanced breast cancer cell sensitivity to chemotherapeutic drugs. We demonstrated that ROS/Nrf2 and p-ERK pathways are two molecular mechanisms involved in the synergistic effect of AEs plus PTX treatment. To highlight the role of ROS herein, we report that the addition of antioxidant N-acetylcysteine (NAC) significantly decreased the antiproliferative effect of the combined treatment. A combined therapy could be able to reduce the dose of chemotherapeutic drugs, minimizing toxicity and side effects. Our results suggest the use of artichoke polyphenols as ROS-mediated sensitizers of chemotherapy paving the way for innovative and promising natural compound-based therapeutic strategies in oncology.